2010
DOI: 10.1027/1614-0001/a000024
|View full text |Cite
|
Sign up to set email alerts
|

Trait and State Components of Perceived Parental Differential Treatment in Middle Adulthood

Abstract: Despite its importance for basic and applied psychology, only a few longitudinal studies have examined whether parental differential treatment (PDT) is a persistent or a transient phenomenon, these studies being confined to childhood or adolescence. Based on latent state-trait theory, the present study identified the amount of variance in three dimensions of perceived PDT in middle adulthood attributable to stable interindividual differences (trait variance) and to intraindividual changes (state variance). At … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 18 publications
(27 reference statements)
0
5
0
Order By: Relevance
“…Previous research on within‐family differences in adulthood has generally involved creating measures in which favoritism and disfavoritism are both conceptualized and operationalized as opposite ends of the same continuum. For example, adult children are often asked to rate themselves relative to a target sibling on dimensions such as closeness, recognition, or provision of support (Boll, Ferring, & Fillipp, , ; Boll, Michels, Ferring, & Filipp, ; Jensen et al, ). Difference scores are then created and used to identify which sibling is “favored,” that is, has a higher score than his or her sibling, or is “disfavored,” that is, has a lower score than his or her sibling.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research on within‐family differences in adulthood has generally involved creating measures in which favoritism and disfavoritism are both conceptualized and operationalized as opposite ends of the same continuum. For example, adult children are often asked to rate themselves relative to a target sibling on dimensions such as closeness, recognition, or provision of support (Boll, Ferring, & Fillipp, , ; Boll, Michels, Ferring, & Filipp, ; Jensen et al, ). Difference scores are then created and used to identify which sibling is “favored,” that is, has a higher score than his or her sibling, or is “disfavored,” that is, has a lower score than his or her sibling.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we examined whether psychological difficulties are associated with low levels of IJ from authority figures in the family, as well. Previously, researchers have explored procedural justice in conflict situations with parents (Brubacher, Fondacaro, Brank, Brown, & Miller, 2009; Fondacaro, Dunkle, & Pathak, 1998; Stuart, Fondacaro, Miller, Brown, & Brank, 2008), parental differential treatment of siblings (Boll, Ferring, & Filipp, 2005; Boll, Michels, Ferring, & Filipp, 2010), and evaluations of equity in inheritance distributions (Drake & Lawrence, 2000) and caregiving responsibilities (Ingersoll-Dayton, Neal, Ha, & Hammer, 2003). In research on the topic of procedural justice from parents, for example, Fondacaro et al (1998) found that young adults’ sense of standing in conflict situations with parents—that is, the degree to which one is treated with dignity and respect by parents—was inversely associated with their deviant behavior and psychological distress.…”
Section: Overview Of Ij and Justice Evaluations In The Familymentioning
confidence: 99%
“…Despite the growing interest in parental favoritism in middle age and beyond, almost all studies have been cross‐sectional; therefore, little is known about how parental preference may change over time. In the only published longitudinal research on this topic, Boll, Michels, Ferring, and Filipp () examined continuity of adult children's perceptions of differential treatment by parents over a relatively short time period (2 years). Their findings suggest that differential treatment is generally a stable characteristic of relationships rather than subject to extensive change over short periods of time.…”
mentioning
confidence: 99%